Latency-associated upregulation of SERBP1 is important for the recruitment of transcriptional repressors to the viral major immediate early promoter of human cytomegalovirus during latent carriage - Poole, Emma; Sinclair, John (Frontiers in Microbiology, 2022)
Suppression of human cytomegalovirus (HCMV) major immediate early gene (IE) expression from the viral major immediate early promoter (MIEP) is known to be crucial for the establishment and maintenance of human cytomegalovirus (HCMV) latency in myeloid progenitor cells and their undifferentiated derivatives. This suppression of the MIEP during latent infection is known to result from epigenetic histone modification imparting a repressive chromatin structure around the MIEP in undifferentiated myeloid cells. In contrast, reactivation, resulting from e.g. myeloid cell differentiation, is associated with activatory chromatin marks around the MIEP. Recently, recruitment of the transcriptional repressor SET1B, via KAP1, to latent HCMV genomes was shown to be involved in latency-associated MIEP suppression in CD34+ progenitor cells. KAP1 is also known to associate with Chromodomain-helicase-DNA-binding protein 3 (CHD3) as part of the NuRD complex which can aid transcriptional silencing. We now show that the cellular protein SERBP1, a known interactor of CHD3, is significantly upregulated during HCMV latency and that this protein is required for MIEP suppression during latent infection of myeloid cells. We further show that SERBP1 mediates CHD3 association with the MIEP as well as KAP1 association with viral genomic DNA. We suggest that SERBP1 functions as a scaffold protein to recruit transcriptional repressors to the latent viral genome and to mediate transcriptional silencing of the MIEP during latent carriage.